OPTIMASI PENGGUNAAN HPMC DAN Na CMC PADA FORMULA TRANSDERMAL PATCH EKSTRAK ETANOL BUNGA TELANG (Clitoria ternatea L.) DENGAN METODE SIMPLEX LATTICE DESIGN - Saryanti, Dwi; Putri Setyadi, Ita Mustika (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Transdermal patch is drug delivery system that is pasted through the skin. These preparations can provide a constant drug release, easy to use, reduce the frequency of drug administration, eliminate first-pass metabolism, and reduce side effects such as gastric irritation and improve patient compliance. Blue pea (Clitoria ternatea L.) contains flavonoid compounds that have anti-inflammatory activity. This study aims to obtain the optimal comparison of HPMC and Na CMC as a polymer in the transdermal patch formula of the ethanol extract of the blue pea (Clitoria ternatea L.). Optimization was carried out using the Simplex Lattice Design method with Software Design Expert version 11. The responses used included pH tests, weight tests, thickness tests, folding tests and moisture content tests. The optimal formula obtained from the Simplex Lattice Design method was verified with the SPSS program using the one sample t-test method. The optimal formula of transdermal patch of blue pea ethanol extract was tested for acceptability to determine whether it was acceptable to the respondent or not. The optimal comparison of HPMC and Na CMC as a polymer with transdermal patch preparation of blue pea ethanol extract was 3.5%:1%, with a desirability value of 0.944.